High levels of mild to moderate depression among men who have sex with men and transgender women in Lima, Peru: implications for integrated depression and HIV care. Issue 12 (2nd December 2022) - Galea, Jerome T.; Marhefka, Stephanie; León, Segundo R.; Rahill, Guitele; Cyrus, Elena; Sánchez, Hugo; Zhang, Zhiwei; Brown, Brandon
ABSTRACT : Depression disproportionally affects people at risk of acquiring or living with HIV and is associated with worse health outcomes; however, depression care is not routinely integrated with HIV prevention and treatment services. Selection of the best depression intervention(s) for integration depends both on the prevalence and severity of depression among potential users. To inform depression care integration in a community-based setting in Lima, Peru, we retrospectively analyzed routinely collected depression screening data from men who have sex with men and transgender women seeking HIV prevention and care services (N = 185). Depression was screened for using the Patient Health Questionnaire-9. Prevalence of any depression (PHQ-9 ≥ 5) was 42% and was significantly associated with the last sexual partner being "casual" ( p = 0.01). Most (81%) depressive symptoms were mild to moderate (≥5 PHQ-9 ≤ 14). Integrating depression care with HIV prevention and treatment services in Peru should begin by implementing interventions targeting mild to moderate depression.